2012
DOI: 10.4236/jbbs.2012.23035
|View full text |Cite
|
Sign up to set email alerts
|

Development of the Gusto Facial Reflex in Perinatally Undernourished Rats

Abstract: In the rat, the taste system plays a critical role in motivating the animal to consume nutrients and avoid toxic substances. In neonatal rat the orofacial movements can be modified by the application of sucrose and quinine in the mouth, producing ingestion or rejection responses, respectively, but there is no information available on the gusto facial reflexes (GFR) under perinatal fasting. The aim of the present study was to determine how undernutrition can affect the development of orofacial responses to sucr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…Furthermore, current data also indicated that the reduced MOF elicited by the different taste concentrations are clearly different when compared to the increased LLF movements to the same gustatory cues. These findings suggest that the neuronal circuits underlying the MOF responses in the UG pups elicited by water and salt reflect different excitability or synaptic organization at this developmental period, because they maintain a relatively constant concentration in the amniotic fluid during gestation [11] [36]. Additionally, on PD1 the UG pups showed consistent LLF reductions in response to all tastants when compare to the CG animals; by contrast on PD3 most of the UG subjects displayed LLF movements in response to the same gustatory cues.…”
Section: Discussionmentioning
confidence: 93%
See 4 more Smart Citations
“…Furthermore, current data also indicated that the reduced MOF elicited by the different taste concentrations are clearly different when compared to the increased LLF movements to the same gustatory cues. These findings suggest that the neuronal circuits underlying the MOF responses in the UG pups elicited by water and salt reflect different excitability or synaptic organization at this developmental period, because they maintain a relatively constant concentration in the amniotic fluid during gestation [11] [36]. Additionally, on PD1 the UG pups showed consistent LLF reductions in response to all tastants when compare to the CG animals; by contrast on PD3 most of the UG subjects displayed LLF movements in response to the same gustatory cues.…”
Section: Discussionmentioning
confidence: 93%
“…Additionally, on PD1 the UG pups showed consistent LLF reductions in response to all tastants when compare to the CG animals; by contrast on PD3 most of the UG subjects displayed LLF movements in response to the same gustatory cues. These findings suggest that in the UG pups the undernutrition interfered more with the synaptic connectivity and the excitability of the circuit underlying the LLF movements [11] [33] [37].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations